(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
This paper presents an original reaction kinetics model as a tool for estimating the carbon yield in hydrothermal carbonization (HTC) of biomass. The kinetics model was developed in MATLAB. The reaction pathways described through a model, in which biomass is converted into solid, liquid and gaseous products. Runge-Kutta method was used to solve the 4 equations derived from the reaction suggestion, through the estimation of 6 Arrhenius kinetics parameters (k1, k2, k3, k4, k5, and k6). The HTC reaction pathway was described through a lumped model, in which biomass is converted into three phase, residual solid, liquid and gaseous products. By choosing the values of k1 and others k values and modelling predictions are in the good of the figure pattern. The k values gave good pattern of figure 3 were k1 = 0.3, k2=0.1, k3=0.3, k4=0.1, k5=0.2, and k6=0.1. They resulted that the biomass conversion was very high about of 90%, carbon content of 39%, liquid content of 24, and gaseous content of 30%.